Protein Kinase C and Oxidative Stress in an Animal Model of Mania - Valnier Steckert, Amanda; Silva Valvassori, Samira; Mina, Francielle; Lopes-Borges, Jessica; Bitencourt Varela, Roger; Kapczinski, Flavio; Dal-Pizzol, Felipe; Quevedo, Joao (Current Neurovascular Research, 2012)
The present study aims to investigate the effects of protein kinase C using the inhibitor Tamoxifen (TMX) on oxidative stress in a rat animal model of mania induced by d-amphetamine (d-AMPH). In the reversal model, d-AMPH or saline (Sal) were administered to rats for 14 days, and between days 8-14, rats were treated with TMX or Sal. In the prevention model, rats were pretreated with TMX or Sal, and between days 8-14, d-AMPH or Sal were administrated. In both experiments locomotor activity and risk-taking behavior were assessed by open-field test and oxidative stress was measured in prefrontal, amygdala, hippocampus and striatum. The results showed that TMX reversed and prevented d- AMPH-induced behavioral effects. In addition, the d-AMPH administration induced oxidative damage in both structures tested in two models. The TMX was able to reverse and prevent this impairment, however in a way dependent of cerebral area and technique evaluated. These findings reinforce the hypothesis that PKC play an important role in the pathophysiology of BD and the need for the study of inhibitors of PKC as a possible target for treatment the BD.
Keywords: Amphetamine